Pelanggaran Kode Etik oleh Hakim Konstitusi dalam Perspektif Etika Profesi Hukum : Studi Kasus Hakim Konstitusi Anwar Usman - Aurelya Putri Alzahrah; Kayus Kayowuan Lewoleba (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The ethical violation committed by Constitutional Court Justice Anwar Usman in the Constitutional Court Decision No. 90/PUU-XXI/2023 underscores the urgent need to strengthen ethical oversight mechanisms to safeguard the integrity of the judiciary. This article analyzes the ethical breach and its implications for public trust and the legitimacy of the Constitutional Court as the guardian of the Constitution. The research employs a normative legal method with statutory, case, and conceptual approaches. The findings indicate that violations of the principles of impartiality, independence, and integrity not only tarnish the image of individual justices but also erode public confidence in the constitutional justice system. Therefore, systemic reform and greater transparency in the enforcement of judicial codes of ethics are essential to restoring the moral authority and professionalism of Indonesia’s highest judicial institution.